Influence of Teacher Behavior on Tertiary Students' Learning and Motivation: A Phenomenological Study - D' Cruz, Donicia (2015)
There is a dearth of studies on students’ perceptions and particularly tertiary students’ perspectives of positive teacher behaviors which influence learning in the classrooms. This qualitative phenomenological study involved 35 tertiary student participants enrolled across six faculties within an institution of higher learning in Malaysia. Data for this phenomenological study was collected through the conducting of focus group discussions with students, individual student interviews, and student journal recordings. Open coding was employed in data analysis of emerging themes and categories. The objective of this qualitative study was to research in-depth tertiary students’ perceptions of teachers’ verbal and nonverbal behaviors and teachers’ pedagogical versatility and style which have influence on students’ learning in the classroom. The primary conceptual framework of this study was predicated on Rosenthal’s teacher expectation effect. The study found that students were influenced by teachers who held high expectations of students, who treated students well, who demonstrated professional behaviors in the classroom, who used caring behaviors, and who motivated students to succeed in their studies. On the converse, the study found, students were demotivated by teachers who demonstrated racism, showed favoritism, demonstrated negative disposition, showed dysfunctional communication skills, and ineffective teaching techniques. The findings of this study are significant in showcasing the benefits of students’ perceptions being employed as an academic compass in guiding teachers to deliver positive and effective teaching behaviors. The insights gleaned from students’ perceptions would contribute toward transformational classroom experiences, producing graduates who will positively benefit Malaysia. This study will serve as a guide and will benefit teachers, educational institutions, and teacher training colleges, to provide quality teaching in academe which translates to, the delivery of quality education for students.